Effects of dopamine antagonists and agonist on cultured human Tenon's fibroblast cells - Wu, K Y; Hong, S J; Chung, Y M (The Kaohsiung journal of medical sciences, 1996)
It was found that long-term therapy with topical antiglaucoma drugs may increase the number of fibroblasts and inflammatory cells in the conjunctiva and Tenon's capsule then decrease the success of glaucoma filtering surgery. Since some dopamine antagonists and agonists are reported to have ocular hypotensive effects, they could potentially be used as clinical antiglaucoma agents in future. In this study, several dopamine antagonists and agonists were evaluated in their effects on the fibroblast proliferation of ocular tissues with cultured human ocular Tenon's fibroblast cells. It was found that dopamine antagonists inhibited [3H]-thymidine uptake to 10.8%, 14.4%, 42.2% and 72.4% of control in domperidone, 28.6%, 67.7%, 96.9% and 99.2% in haloperidol, 9.8%, 18.9%, 103.5% and 104.6% in moperone and 9.8%, 24.7%, 70.8% and 96.9% in loxapine respectively, while the 0.5% concentration of drugs were dissolved in dimethyl sulfoxide (DMSO) followed by dilution in culture medium to final concentrations ranging from 0.05%, 0.005%, 0.0005% to 0.00005%. In the case of dopamine agonist, bromocriptine, the proliferation of cultured human Tenon's fibroblast cells was also inhibited for 25.1% of the control at 0.05% concentration and 92.3% of the control at 0.00005% concentration. These results indicate that these dopamine drugs have a potential long-term application in the treatment of glaucoma without having the stimulating effect on the proliferation of human Tenon's fibroblast cells.